2015
DOI: 10.1016/j.stem.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

TPO-Induced Metabolic Reprogramming Drives Liver Metastasis of Colorectal Cancer CD110+ Tumor-Initiating Cells

Abstract: Liver metastasis is a leading cause of death in patients with colorectal cancer. We previously found that colorectal cancer tumor-initiating cells (TICs) expressing CD110, the thrombopoietin (TPO)-binding receptor, mediate liver metastasis. Here, we show that TPO promotes metastasis of CD110+ TICs to the liver by activating lysine degradation. Lysine catabolism generates acetyl-CoA, which is used in p300-dependent LRP6 acetylation. This triggers tyrosine phosphorylation of LRP6, ultimately activating Wnt signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 39 publications
3
99
0
Order By: Relevance
“…In an in de pen dent study [187], metasta tic breast can cer cells with a se lec tive tro pism for the brain dis played in creased gly col y sis cou pled to TCA cy cle and in creased mi to chon dr ial res pi ra tion, PPP flux and fatty acid β ox i da tion com pared to parental cir cu lat ing can cer cells. These ev i dences sug gest that there might be a high de gree of or gan se lec tiv ity in the se lec tion of meta bolic traits en abling suc cess ful metasta tic dis sem i na tion [200].…”
Section: Metabolic Contribution To Cancer Metastasismentioning
confidence: 99%
“…In an in de pen dent study [187], metasta tic breast can cer cells with a se lec tive tro pism for the brain dis played in creased gly col y sis cou pled to TCA cy cle and in creased mi to chon dr ial res pi ra tion, PPP flux and fatty acid β ox i da tion com pared to parental cir cu lat ing can cer cells. These ev i dences sug gest that there might be a high de gree of or gan se lec tiv ity in the se lec tion of meta bolic traits en abling suc cess ful metasta tic dis sem i na tion [200].…”
Section: Metabolic Contribution To Cancer Metastasismentioning
confidence: 99%
“…More recently, it has been identified that CR-CSCs have a role as drivers of the metastatic progression of colorectal cancer4. Moreover, the expression of the CD44v6 variant of CD44 or CD110 was shown to serve as a biomarker for this CR-CSC pool of colorectal metastasis drivers56. These studies started to unravel the mechanisms involved in the regulation of CR-CSCs associated with metastasis and showed that plasticity between CR-CSCs and non-CR-CSCs occurs at advanced stages of tumor progression.…”
mentioning
confidence: 99%
“…Furthermore, lysine catabolism in these cells promoted the generation of glutamate, which enhances cysteine uptake and GSH synthesis. Thus, CD110 + CSCs are able to modulate their redox status by lysine catabolism, promoting self-renewal, drug-resistance and liver metastasis (Wu et al, 2015). …”
Section: Metabolic Phenotypes Of Scs and Cscsmentioning
confidence: 99%